Para una sociología de la emancipación mental - Chávez, Juan Miguel; García, Gonzalo (Ariadna Ediciones, 2020)
The following work proposes an overview of what we could consider as one of the guiding problems for Latin American reflection in the first half of the 20th century (and, as argued in the same chapter, throughout the development of the Latin American thought): the question of authenticity. I know It deals with a problem in which José Gaos played a fundamental role; not only for wondering from his residence in Mexico about what (Latin) American of our philosophical tradition, but because he was the teacher trainer of the following generations that assumed as a cultural task the question of a properly Latin American philosophy-Highlighting the figure of Leopoldo Zea. Curiously In this perspective, Chilean philosophy will only find out in the second mid-twentieth century with Félix Schwartzmann and Luis Oyarzún, who put Chile, from a tradition different from that of Gaos, as place of enunciation. Juan Miguel Chávez and Gonzalo García propose that the desire for authenticity continues to operate in the proposals current that have revitalized the tradition of the essay; even more, they point out that it is a recursive topic in the history of comings whose. An attempt at explanation leads to the sociology of knowledge.